The spatial density distribution of the ion flux in the laser-plasma source for deposition of nanocoating on substrates of increased size - Goncharov, Victor K.; Puzyrev, Michail V.; Stupakevich, Valery Yu.; Shulhan, Nikita I. (Journal of the Belarusian State University. Physics, 2021)
The present work is devoted to the experimental determination of the uniformity of the ion flux density on a substrate with an increased size ( 200 cm2 ) in order to form nanostructures by the laser-plasma method. The system for deposition of nanostructures consists of an erosion laser torch of the target material and a substrate located in a vacuum chamber. For smooth adjustment of the parameters of the deposited particles on the substrate, a grid is located between the laser target and the substrate, on which a negative potential is applied relative to the laser target. As a result, a particle stream is formed after the grid, consisting mainly of ions, whose energy can be reliably and smoothly controlled by applying a positive potential to the grid in relation to the substrate. Experiments have shown that the uniformity of the density of ion fluxes on a substrate of increased size ( 200 cm2 ) in a laser-plasma source for nanocoating can be increased by applying an accelerating potential to the substrate in relation to the grid. The minimum difference between the ion flux density in the center of the target and at its edge can be reduced to 5 %. As a result, it is technologically possible to clean the surface of the substrate with ions of the laser target material (secondary emission), create a pseudodiffusion layer of the target material in the near-surface region of the substrate, and apply the laser target material to the substrate. At the same time, all these operations can be performed sequentially without depressurising the vacuum chamber. This allows obtaining coating with good adhesion on substrates of increased size.